Tracked Changes. Aerospace series. Cable outlet accessories for circular and rectangular electrical and optical connectors. Cable outlet, style K, straight, for heat shrinkable boot, shielded, sealed, self-locking - Product standard Part 063, (22nd July 2022) - British Standards Institution,
No abstract available